2022
DOI: 10.3390/children9081121
|View full text |Cite
|
Sign up to set email alerts
|

Mid–Long-Term Outcomes of Surgical Treatment of Legg-Calvè-Perthes Disease: A Systematic Review

Abstract: Background: Legg–Calvè–Perthes disease (LCPD) is a common childhood disease that usually occurs in 4- to 12-year-old children. Surgical treatment consists of femoral, pelvic, or combined osteotomies. This comprehensive review aimed to investigate the mid- and long-term outcome of the surgical treatment. Methods: A systematic review of PubMed, Science Direct, and MEDLINE databases was performed by two independent authors, using the keywords “outcome”, “surgical treatment”, “pelvic osteotomy”, “femoral osteotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…At present, there is not other relevant literature to report the cut off value of ATD requires surgical treatment. It is generally believed that the effect of trochanter arrest surgery before 6-8 years old is better than that after 8 years old [15][16][17] , which is similar to the results of k − male and k − female proposed by us. K represents the growth rate of the greater trochanter at all ages.…”
Section: Discussionsupporting
confidence: 82%
“…At present, there is not other relevant literature to report the cut off value of ATD requires surgical treatment. It is generally believed that the effect of trochanter arrest surgery before 6-8 years old is better than that after 8 years old [15][16][17] , which is similar to the results of k − male and k − female proposed by us. K represents the growth rate of the greater trochanter at all ages.…”
Section: Discussionsupporting
confidence: 82%
“…At present, it is generally believed that the effect of trochanter arrest surgery before 6-8 years old is better than that after 8 years old [15][16][17] , which is similar to the results of k − male and k − female proposed by us. K represents the growth rate of the greater trochanter at all ages.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown the severity of initial disease is a main factor affecting the prognosis of patients with LCPD 25 . The lateral pillar classi cation usually predicts the severity of the radiographic outcome 24,[26][27][28] .…”
Section: Discussionmentioning
confidence: 99%